Strength evaluation of concrete corbels cast in a different stage from the column - ARAÚJO,D. L. (2017)
Abstract The design of a precast structural system requires joints between the structural elements, and concrete corbels are commonly used in the connection between beams and columns. Concrete corbels create an obstacle in the optimization of precast production, mainly of columns that have two or more concrete corbels in different faces. In these cases, the concrete corbels need to be manufactures in a different stage from the column, which requires attention to the interface between column and corbel, and some solution to ensure the continuity of the main tie reinforcement. For this paper, tests were conducted along with analytical and computational modeling of five concrete corbels models: one monolithic model and four where the corbels are manufactured in a different stage from the column. Results show the failure mode, the interface gap opening and the accuracy of the analytical and computational predictions. It was observed that the concrete corbels with bent main tie reinforcement displayed the largest gap-opening at the interface and that the computational modeling represented the strength of the monolithic concrete corbel better than the design code models.